Investigation of Attitudes Towards Computer Programming in Terms of Various Variables - Karaci, Abdulkadir (Academy and Industry Research Collaboration Center (AIRCC), 2016)
This study aims to determine the attitudes of individuals towards computer programming in terms of
various variables. The study group consists of the students of Kastamonu University Department of
Computer Education and Instructional Technologies Teaching (CEIT), Department of Computer
Engineering, and Department of Computer Programming. Data were collected via Attitude towards
Computer Programming Scale (AtCPS).The results of this study show that students have neutral attitudes
towards computer programming in general. Male computer programming students have significantly
higher attitudes towards programming in comparison to female computer programming students. In
addition, attitude towards computer programming statistically varies by grade. The higher is grade, the
lower is attitude. The more time CEIT and computer programming students spend on computer for
programming purposes daily, the more positive attitudes they have towards programming. Attitude
significantly varies by graduated high school only among CEIT students
Keywords: Programming; attitude towards programming; attitude scale; 4. Education